The impact of technological advance on resources cataloging improvement in Monographs Department - Pacholska, Hanna (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article discusses the impact of computerization and Wrocław University Library reorganization on the activities of Monographs Department. It offers an insight into the opportunities of VIRTUA system clients in book cataloging and into the building a field of activity as based on Wrocław University Library homepage, NUKAT Center, and the Internet (on the basis of the author's own professional experience as a cataloger).
Keywords: shared cataloging; VIRTUA; library resources cataloging; technological advance; Wrocław University Library; Monographs Department